Make them think in the Digitalized Era: Developing Critical Thinking Skills Using Technology - Anu, P.; Bhaskaran Nair, P. (International Journal of Psychosocial Rehabilitation, 2019)
Critical thinking is a term that involves more than just thinking about something critically. It is a general concept that can be applied in any discipline and practice requiring the use of agreed means of collecting and using knowledge to develop solutions expressed from multiple points of view.In the current computerized age, anybody can distribute any data on their sites, internet based life stages, and other inline gatherings. The reason for this investigation was to recognize the influence of the digital era on the development of critical thinking skills among visual art students from the perspective of instructors so that teaching methods can be adjusted to improve student learning.